Bridging blood cancers and inflammation: The reduced Cancitis model. (21st March 2019) - Ottesen, Johnny T.; Pedersen, Rasmus K.; Sajid, Zamra; Gudmand-Hoeyer, Johanne; Bangsgaard, Katrine O.; Skov, Vibe; Kjær, Lasse; Knudsen, Trine A.; Pallisgaard, Niels; Hasselbalch, Hans C.; Andersen, Morten
Highlights: A model of avascular cancer coupled with innate and adaptive immune response. Normal and malignant stem cells, mature cells, dead cells and immune cells are included. Impact of exogenous inflammatory stimuli, treatments, and resistance to effector immune cells is shown. The model is validated for Philadelphia negative, JAK2V617F positive MPNs on cytokine data. A dimensionless form and a model reduction by Fenichel theory from 6 to 2-dimensions are shown. Abstract: A novel mechanism-based model - the Cancitis model - describing the interaction of blood cancer and the inflammatory system is proposed, analyzed and validated. The immune response is divided into two components, one where the elimination rate of malignant stem cells is independent of the level of the blood cancer and one where the elimination rate depends on the level of the blood cancer. A dimensional analysis shows that the full 6-dimensional system of nonlinear ordinary differential equations may be reduced to a 2-dimensional system - the reduced Cancitis model - using Fenichel theory. The original 18 parameters appear in the reduced model in 8 groups of parameters. The reduced model is analyzed. Especially the steady states and their dependence on the exogenous inflammatory stimuli are analyzed. A semi-analytic investigation reveals the stability properties of the steady states. Finally, positivity of the system and the existence of an attracting trapping region in the positive octahedron guaranteeing global existence and uniqueness of solutions are proved. The possible topologies of the dynamical system are completely determined as having a Janus structure, where two qualitatively different topologies appear for different sets of parameters. To classify this Janus structure we propose a novel concept in blood cancer - a reproduction ratio R . It determines the topological structure depending on whether it is larger or smaller than a threshold value. Furthermore, it follows that inflammation, affected by the exogenous inflammatory stimulation, may determine the onset and development of blood cancers. The body may manage initial blood cancer as long as the self-renewal rate is not too high, but fails to manage it if an inflammation appears. Thus, inflammation may trigger and drive blood cancers. Finally, the mathematical analysis suggests novel treatment strategies and it is used to discuss the in silico effect of existing treatment, e.g. interferon- α or T-cell therapy, and the impact of malignant cells becoming resistant.